(untitled) (Iranian Journal of Kidney Diseases, 2020)
No large study has been conducted on biopsy-proven nephropathies. Our aim was to report clinical and pathological pattern of kidney disease diagnosed by kidney biopsy in our center. This is a retrospective study on kidney biopsy during 7 years; we analyzed the results of kidney biopsies and their clinical data. Data were analyzed by SPSS 18.0 and a P < .05 was considered. In 1355 kidney biopsies (55.7% women, age = 33.2 ± 16.4), primary glomerulonephritis (GN) was the main feature (57.1%). The most common presentation was asymptomatic urine abnormality (32.3%). Lupus nephritis (24.5%), membranous GN (17.0%), and focal segmental glomerulosclerosis (13.9%) were the most frequent diagnosis. This study highlights the histopathological patterns of kidney disease in southern Iran. lupus nephritis, membranous GN, and focal segmental glomerulosclerosis are currently the three major diseases. These results have an important role in organizing renal health plans as an initial phase in our population.